IMPLEMENTASI PENDIDIKAN KARAKTER DALAM PEMBELAJARAN AKIDAH AKHLAK SECARA DARING PADA SISWA KELAS X MA DARUL FAIZIN CATAKGAYAM MOJOWARNO JOMBANG - Fitriyah, Nurul; Surur, Shobihus (Program Studi Pendidikan Agama Islam, Fakultas Agama Islam, Universitas Hasyim Asy'ari Tebuireng Jombang, Indonesia, 2022)
Abstract: This study aims to realize a common desire to be able to know the abilities and character of students and develop the personality of students, both in the fields of knowledge, religion and spirituality in the three teaching and learning processes in the madrasa environment. This research puts forward a qualitative approach pattern and aims to gain insight into something. This research is contained in a case study by analyzing several things related to character education in online learning at Madrasah Aliyah Darul Faizin catakgayam mojowarno jombang. The data sources of this research were obtained through documentation, interviews and field observations, which were then processed systematically and concluded. The results of this study obtained the following conclusions: 1). The concept of character education in learning morals, 2). The process of learning morality online at Madrasah Aliyah Darul Faizin School, 3). The implementation of character education in online learning of moral creed at Madrasah Aliyah Darul Faizin is considered less than optimal.